1995
DOI: 10.1139/b95-370
|View full text |Cite
|
Sign up to set email alerts
|

The structure of chitinases and prospects for structure-based drug design

Abstract: Many fungi, including pathogenic strains, require proper chitin metabolism to assure normal cell wall replication. Chitinase hydrolyzes chitin; inhibition of endogenous chitinases or application of extracellular chitinases can disrupt fungal division. It is possible that chitinase inhibitors could be used as antifungal agents. We have solved the X-ray structure of a class I1 chitinase from barley and proposed a mechanism of action. The enzyme has a structural core similar to lysozyme and probably acts in a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Allosamidin, 10 ( Figure 2B), and related natural products are pseudotrisaccharide chitinase inhibitors (Sakuda et al, 1986) isolated from the mycelium of Streptomyces sp. Although detailed inhibition and kinetics studies have not been reported, allosamidin is believed to act as a transition state analog (Van Vranken, 1992;Terwisscha van Scheltinga et al, 1995;Robertus et al, 1995). Moreover, allosamidin shows no inhibitory activity against lysozyme (Koga et al, 1987), which is consistent with the suggestion that the two enzymes have different mechanisms (and therefore unique transition states) for hydrolysis.…”
Section: Transition State Inhibitorsmentioning
confidence: 56%
See 1 more Smart Citation
“…Allosamidin, 10 ( Figure 2B), and related natural products are pseudotrisaccharide chitinase inhibitors (Sakuda et al, 1986) isolated from the mycelium of Streptomyces sp. Although detailed inhibition and kinetics studies have not been reported, allosamidin is believed to act as a transition state analog (Van Vranken, 1992;Terwisscha van Scheltinga et al, 1995;Robertus et al, 1995). Moreover, allosamidin shows no inhibitory activity against lysozyme (Koga et al, 1987), which is consistent with the suggestion that the two enzymes have different mechanisms (and therefore unique transition states) for hydrolysis.…”
Section: Transition State Inhibitorsmentioning
confidence: 56%
“…Moreover, allosamidin shows no inhibitory activity against lysozyme (Koga et al, 1987), which is consistent with the suggestion that the two enzymes have different mechanisms (and therefore unique transition states) for hydrolysis. It was originally proposed that the planar protonated oxazoline ring acts as an oxocarbenium ion transition state analog (Robertus et al, 1995). However, an X-ray structure of hevamine with allosamidin bound in the active site (Terwisscha van Scheltinga et al, 1995) led to the suggestion that allosamizoline (11), the aglycone portion of allosamidin, instead resembles an oxazoline ion reaction intermediate.…”
Section: Transition State Inhibitorsmentioning
confidence: 99%
“…4.5 Design of a New Class of Inhibitor. The inhibition of chitinases has been identified as a possible objective in the development of novel antifungal therapeutics . When considering the rational design of a family 18 chitinase inhibitor, it is useful to identify unique points along the hydrolysis pathway which may be targeted.…”
Section: 0 Discussionmentioning
confidence: 90%
“…Chitinases have been found in a wide range of organisms including bacteria, , plants, fungi, insects, and crustaceans . For those organisms that utilize the structural properties of chitin, chitinases are critical for the normal life cycle functions of molting and cell division. , In addition, plants produce chitinases as a defense against fungal pathogens. , Because chitin is not found in vertebrates, it has been suggested that inhibition of chitinases may be used for the treatment of fungal infections and human parasitosis …”
Section: 0 Introductionmentioning
confidence: 99%
“…For organisms that utilize the structural properties of chitin, chitinases are critical for the normal life-cycle functions of molting and cell division (Fukamizo andKramer 1985, Kuranda andRobbins 1991). Because chitin is not found in vertebrates, inhibition of chitinases is a promising strategy for treatment of fungal infections and human parasitosis (Robertus 1995).…”
Section: Study Of Enzyme Reaction Mechanismsmentioning
confidence: 99%